(untitled) (Interdisciplinary Journal of Nursing and Health, 2024)
Introduction: External ventricular drain (EVD) placement is a common neurosurgical procedure. Nurses play a crucial role in care, troubleshooting, and monitoring of EVD-related complications, making their education and training in this area of paramount importance. A well-trained nurse possesses the necessary knowledge and skills to recognize and respond promptly to EVD-related complications, such as infections, bleeding, and blockages. External ventricular drainage is associated with a high rate of nosocomial meningitis. The introduction of a well- implemented EVD care bundle can significantly decrease EVD infection rates. The support of the multi-item bundle for EVD is considered very important to reduce EVD-related infections. Aim: To summarize the most recent available evidence for the prevention and control of EVD infections. Methods: Comprehensive literature search had been done using the PubMed (Medline), Embase, CINAHL, and Cochrane databases. The narrative review was performed according to the PRISMA Extension for Scoping Review checklist (PRISMA-ScR). Results: The query identified 4266 studies; after duplicate removal and exclusion of papers due to non-pertinent criteria, 26 studies were included. Only three papers were related to pediatric patients and all were about EVD anchoring. Regarding the risk of infection, bundles and protocols are important for the reduction of the occurrence rate; however, staff adherence to these is fundamental. Conclusion: Multidisciplinary staff and training are fundamental to improve EVD management. Avoiding routine or daily sampling reduces the EVD infection rate. When the procedure is requested, it is important to follow a strict protocol and to use sterile techniques. Hydrocolloid dressings, SecurAcath, gauze, and film dressings were used to anchor the cover EVD in the studies.